Targeting autophagy using small-molecule compounds to improve potential therapy of Parkinson's disease - Kai Zhang; Shiou Zhu; Jiamei Li; Tingting Jiang; Lu Feng; Junping Pei; Guan Wang; Liang Ouyang; Bo Liu (Elsevier, 2021)
Parkinson's disease (PD), known as one of the most universal neurodegenerative diseases, is a serious threat to the health of the elderly. The current treatment has been demonstrated to relieve symptoms, and the discovery of new small-molecule compounds has been regarded as a promising strategy. Of note, the homeostasis of the autolysosome pathway (ALP) is closely associated with PD, and impaired autophagy may cause the death of neurons and thereby accelerating the progress of PD. Thus, pharmacological targeting autophagy with small-molecule compounds has been drawn a rising attention so far. In this review, we focus on summarizing several autophagy-associated targets, such as AMPK, mTORC1, ULK1, IMPase, LRRK2, beclin-1, TFEB, GCase, ERRα, C-Abelson, and as well as their relevant small-molecule compounds in PD models, which will shed light on a clue on exploiting more potential targeted small-molecule drugs tracking PD treatment in the near future.